1029 FABRY DISEASE: A RARE CAUSE TO REMEMBER WHEN FACING ACUTE KIDNEY INJURY IN YOUNG. (15th December 2022) - Onorato, Federica; Vannelli, Andrea; Parato, Andrea Giovanni; Ricci, Giulia; Morgagni, Riccardo
Abstract: Introduction: Anderson-Fabry disease (FD) is a rare X-linked hereditary disease caused by mutations in the alpha-galactosidase A (GLA) gene, a lysosomal hydrolase that catabolizes lipids. GLA deficency leads to a progressive accumulation of undegraded glycosphingolipids, mainly Globotriaosylceramide (GB3), within lysosomes of cells (epithelial and endothelial cells, neurons, cardiomyocytes and renal cells), leading to cellular dysfunction. The incidence of FD is 1:117.000 but in patients with end stage renal disease (ESRD), incidence is higher, ranging from 0.04% up to 1.16% in male dialysis patients. Classical form of the disease shows renal, cardiac and cerebrovascular involvements usually. Cardiac involvement includes hypertrophic cardiomyopathy, arrhythmias such as complete heart block, valve dysfunction and myocardial infarction. Renal manifestations include proteinuria, progressive loss of renal function with chronic kidney disease (CKD) that leads to ESRD. The diagnosis of FD can be very difficult and often is delayed due to subtle clinical manifestations, but an early diagnosis is crucial to start enzyme replacement therapy (ERT), based on recombinant human GLA, as soon as possible. Clinical Case: we describe the case of a 36-years-old male admitted to the Emergency Room of our hospital due to asthenia, nausea, dysphagia, anuria and loss of weight. At physical examination, apical systolic murmur and a bilateral ankle edema. Blood pressure was 195/100 mmHg, heart rate 125 beats per minute, peripheral oxygen saturation 100%. Blood test showed Hemoglobin 8 g/dL, Blood Urea 422 mg/dL, Creatinine 20 mg/dL, Na+ 135 mEq/L, K+ 4 mEq/L, Phosphorus 9 mg/dL. Arterial blood gas analysis showed metabolic and lactic acidosis. The diagnosis of acute kidney injury (AKI) was made, and a dialytic treatment was scheduled. During dialytic session, the patient had a syncope. EKG showed a complete left bundle branch block (LBBB) with advanced atrio-ventricular block (2:1, complete). An echocardiogram highlighted a severe myocardial hypertrophy (septal wall 25 mm) involving also the right ventricle with "ground glass" aspect of the posterolateral, posterior and inferior septum, with minimal pericardial effusion. Heart MRI scan confirmed LV myocardial hypertrophy with circumferential aspect (interventricular septum 26.6 mm), mild decrease in left ventricular ejection fraction (47%) and myocardial hypointensity area in the FSE sequences. Renal ultrasound showed bilateral cortical hyperecogenity, small cortico-medullary border, initial reduction of kidney volume and diffuse perirenal edema. In consideration of the high probability of a storage disease, we performed genetic testing for FD and Gaucher disease, peri-umbilical fat biopsy for Amyloid Disease and a renal biopsy. The genetic test resulted positive for typical mutation of FD and renal biopsy documented ESRD secondary to glycosphingolipid storage disease ceramid type from FD. Conclusion: Differential diagnosis of AKI in a young male should include FD, as suggested by the clinical case reported, and nephrologist should screen young patients for α-GLA enzyme deficiency (diagnostic for FD) possibly coupled with renal biopsy in uncertain cases.